Badan Usaha Milik Desa sebagai Badan Hukum - Sisworini, Desi Fadikta; Rumawi, Rumawi (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2025)
Village Owned Enterprises which are often called BUMDes can be interpreted as a form of business run by and government system. Policies in village-owned enterprise regulations have changed a lot from time to time. Law number 11 of 2020 concerning village-owned enterprises is the final rule regarding the development, establishment, mechanism and status of village-owned enterprises, which in turn is government regulation number 11 of 2021 is the implementing regulation. Thus it is necessary to examine the nature of bumdes law based on the Perpu. The focus of the research is first, what is the legal nature of village-owned enterprises according to government regulation number 11 of 2021 concerning village-owned enterprises? secondly, can a village-owned enterprise be classified as a legal entity? This study uses normative legal research methods with statutory and conceptual approaches. The conclusion from this research is the nature of BUMDes law based on Permen number 11 of 2021, namely regarding the establishment and management objectives of BUMDes based on Law number 11 of 2020. Whereas BUMDes itself is a public legal entity. To the village government to maximize the management of BUMDes in accordance with applicable regulations. Regulations regarding BUMDes are updated according to the needs and position of BUMDes.